Alterations in the blood count of canine diagnosed with breast neoplasms attended at the Clinical Center Veterinary of UNIPAM (Research, Society and Development, 2022)
Neoplasms are increasingly present in the daily life of veterinary clinics, among these, breast cancer represents about 50 to 70% of the cases attended. In the blood count of these animals it is possible to identify parameters that not only match the animal's health, but also monitor the regression or evolution of the disease. The aim of this study was to characterize the epidemiological profile and identify the main changes in the blood count of bitches with breast cancer attended at the Clinical Veterinary Center of UNIPAM. The clinical records for the period from 2017 to 2020 were evaluated and the factors of age, race, castration and blood count were investigated. 316 clinical records were analyzed. It was observed that bitches in the senile phase with mean of 9.8 years, SRD 60.7% (192/316) and 82.8% (259/316) not neutered, had a greater predisposition to develop breast cancer. In the hematological picture, lymphopenia was identified, representing 37.6% (119/316), anemia 29.7% (94/316) and leukocytosis 22.1% (70/316). It is concluded that lymphopenia was the most significant alteration, followed by normocytic normochromic anemia and leukocytosis due to neutrophilia with a left shift.